Conio, replica, valore - Finocchi, Riccardo; Perri, Antonio (Rivista Italiana di Filosofia del Linguaggio, 2014)
The concept of replicability has always crossed the basic relationships between discourses, money, rites established by philosophy and humanities. In this paper a critique of the idea of coinage (and the concept of token) is developed, grounding on a philosophical rather than philological approach. We argue about the fundamental role played by a positive definition of money value, which is indeed also the core of any social praxis institutionally constituted through replicability. The «double essence» of value in Saussure is so reconstructed as to make it a sort of paradigm of any social ontology and practice of technical reproducibility. In any case, the growing invasion of digital reproducibility is deemed to weaken ‘the same’ (the replica): it will become more and more ‘identical’, indistinguishable (as in the coinage), therefore reducing replicas to mere relative and negative values. The ‘identical’ without value, then, eclipses any potential of meaning